2023
DOI: 10.1038/s41591-023-02452-y
|View full text |Cite
|
Sign up to set email alerts
|

Mesothelin-targeting T cell receptor fusion construct cell therapy in refractory solid tumors: phase 1/2 trial interim results

Abstract: The T cell receptor fusion construct (TRuC) gavocabtagene autoleucel (gavo-cel) consists of single-domain anti-mesothelin antibody that integrates into the endogenous T cell receptor (TCR) and engages the signaling capacity of the entire TCR upon mesothelin binding. Here we describe phase 1 results from an ongoing phase1/2 trial of gavo-cel in patients with treatment-refractory mesothelin-expressing solid tumors. The primary objectives were to evaluate safety and determine the recommended phase 2 dose (RP2D). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…We thus developed a migration strategy to enhance the infiltration of CAR T cells into solid tumors. Mesothelin CARs have the potential to ameliorate outcomes in many different solid tumor cancers, such as ovarian, pancreatic, and lung among others 5,6,31 . Engineering increased infiltration of mesothelin-targeted CARs has been demonstrated to enhance therapeutic outcomes in immune excluded solid tumors 16 .…”
Section: Resultsmentioning
confidence: 99%
“…We thus developed a migration strategy to enhance the infiltration of CAR T cells into solid tumors. Mesothelin CARs have the potential to ameliorate outcomes in many different solid tumor cancers, such as ovarian, pancreatic, and lung among others 5,6,31 . Engineering increased infiltration of mesothelin-targeted CARs has been demonstrated to enhance therapeutic outcomes in immune excluded solid tumors 16 .…”
Section: Resultsmentioning
confidence: 99%
“…Gavocabtagene autoleucel, a mesothelin-targeting T cell receptor fusion construct, was evaluated recently in a phase I/II clinical trial (NCT03907852) in patients with selected refractory solid tumors expressing mesothelin (malignant pleural mesothelioma, ovarian cancer, and cholangiocarcinoma) and has shown clinical activity with an ORR of 20% and a 6-month OS rate of 70%. Grade ≥ 3 pneumonitis and cytokine release syndrome were observed in 16% and 25% of patients, respectively [103]. Similar efforts are underway to develop ACTs targeting CTAs, and these treatments can potentially be considered for evaluation in patients with TETs in the future [104][105][106].…”
Section: Cell-based Therapiesmentioning
confidence: 99%
“…TRuCs comprise one T cell receptor (TCR) subunit attached to a costimulatory domain and integrated into native CD3 complexes via transduction. Upon the recognition of the specific tumor antigen, TRuCs facilitate the activation of the entire TCR independent of HLA stimulation [17]. In vitro, anti-mesothelin TRuC T cells have demonstrated effective cytotoxicity against different cancer cell lines with high mesothelin expression including mesothelioma, NSCLC, and ovarian adenocarcinoma tumor cells.…”
Section: Mesothelinmentioning
confidence: 99%
“…Interim data from a phase 1/2 study of gavo-cel after lymphodepletion in patients with treatment-refractory MPM showed an ORR of 21%, a median PFS of 5.6, and a median OS of 11.2 months (NCT03907852). Grade 3 or higher pneumonitis and cytokine release syndrome were observed in 0% and 15% of patients at the recommended phase 2 dose (RP2D) [17]. Gavo-cel is the first targeted therapy to demonstrate tumor response in MPM.…”
Section: Mesothelinmentioning
confidence: 99%